Factors Affecting Online Teachers’ Satisfaction Amid the COVID-19 Pandemic - Thach, Pham Ngoc; Huong, Do Quynh; Thanh, Tran Minh (VNU Journal of Science: Education Research; Vol 37 No 1, 2021)
This study explores the factors that affect lecturers’ satisfaction when teaching online during the period of the COVID-19 pandemic at a big university in Vietnam using mixed methods approach, frequency analysis, correlation and multivariate regression techniques. The study results show that the main factors affecting lecturers’ satisfaction were their interaction with students, their technology skills, institution support and students’ online behaviour. The results of qualitative data analysis (open-ended questions and interviews) reinforced the above findings and indicated the need to deploy blended-learning, which combines online and face-to-face teaching modes to ensure quality of teaching and to enhance lecturers’ satisfaction in the future digitalization in higher education institutions.